THE SIGNIFICANCE OF THE COURAGE AND HIGH ENDURANCE SHOWN BY OUR PEOPLE IN THE YEARS OF WORLD WAR II IN PATRIOTIC EDUCATION OF THE YOUNG PEOPLE (American Journal of Interdisciplinary Research and Development, 2023)
One of the most complex and responsible tasks of the initial period of the Soviet-German war was to put the economy on a military track.